2015
DOI: 10.1186/s12967-015-0440-1
|View full text |Cite|
|
Sign up to set email alerts
|

Total saponin from Anemone flaccida Fr. Schmidt abrogates osteoclast differentiation and bone resorption via the inhibition of RANKL-induced NF-κB, JNK and p38 MAPKs activation

Abstract: Osteoclasts, bone-specialized multinucleated cells, are responsible for bone destructive diseases such as rheumatoid arthritis and osteoporosis. Natural plant-derived products have received substantial attention given their potential therapeutic and preventive activities against bone destructive diseases. In the present study, we investigated the effects of total saponin (TS) from Anemone flaccida Fr. Schmidt, on receptor activator of nuclear factor-κB ligand (RANKL)-induced in vitro osteoclast differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…The RANKL-RANK interaction results in the phosphorylation of MAPKs, including JNK, p38 and ERK, promoting the activation of c-Fos and facilitating the translocation of activator protein-1, an essential translation factor for osteoclast formation. Previous studies have confirmed that inhibitors of p38, JNK or ERK inhibit osteoclast formation (46,47). In the present study, ZOL diminished the phosphorylation of JNK induced by RANKL.…”
Section: Discussionmentioning
confidence: 67%
“…The RANKL-RANK interaction results in the phosphorylation of MAPKs, including JNK, p38 and ERK, promoting the activation of c-Fos and facilitating the translocation of activator protein-1, an essential translation factor for osteoclast formation. Previous studies have confirmed that inhibitors of p38, JNK or ERK inhibit osteoclast formation (46,47). In the present study, ZOL diminished the phosphorylation of JNK induced by RANKL.…”
Section: Discussionmentioning
confidence: 67%
“…Osteoclasts are bone-specialized multinucleated cells and are responsible for bone-destructive diseases, such as rheumatoid arthritis and osteoporosis. In RAW264.7 cells and CIA rats, the total saponin (TS) of A. flaccida concentration-dependently inhibited receptor activator of NF- κ B ligand (RANKL)-induced osteoclast formation and bone marrow-derived macrophages (BMMs), as well as decreased extent of actin ring formation and lacunar resorption 6 , 37 . The RANKL-stimulated expression of osteoclast-related transcription factors was also diminished by TS, while the expression of osteoprotegerin (OPG), at both mRNA and protein levels increased, and the ratio of RANKL to OPG in inflamed joints and sera of CIA rats decreased 37 .…”
Section: Bioactivitiesmentioning
confidence: 99%
“…The state-of-the-art methods have been adopted to isolate bioactive chemical constituents from Anemone species following bioactivity-directed fractionation 4 , 5 . Some modes of action of bioactive extracts or compounds of Anemone species have been established 6 , 7 . However, a comprehensive review of the Anemone medicinal resources is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…TRAF6 is closely associated with the maturation and differentiation of osteoclasts in vitro (20). Recent studies have reported that TRAF6 serves an important role in the development, invasion and metastasis of tumors by activating nuclear factor (NF)-κb (21,22). however, studies regarding the expression of TRAF6 in osteosarcoma and its biological role are rare.…”
Section: The Effects Of Traf6 On Proliferation Apoptosis and Invasiomentioning
confidence: 99%